New insights of platelet endocytosis and its implication for platelet function - Zhou, Yangfan; Dong, Jianzeng; Wang, Mengyu; Liu, Yangyang (Frontiers in Cardiovascular Medicine, 2024)
Endocytosis constitutes a cellular process in which cells selectively encapsulate surface substances into endocytic vesicles, also known as endosomes, thereby modulating their interaction with the environment. Platelets, as pivotal hematologic elements, play a crucial role not only in regulating coagulation and thrombus formation but also in facilitating tumor invasion and metastasis. Functioning as critical components in the circulatory system, platelets can internalize various endosomal compartments, such as surface receptors, extracellular proteins, small molecules, and pathogens, from the extracellular environment through diverse endocytic pathways, including pinocytosis, phagocytosis, and receptor-mediated endocytosis. We summarize recent advancements in platelet endocytosis, encompassing the catalog of cargoes, regulatory mechanisms, and internal trafficking routes. Furthermore, we describe the influence of endocytosis on platelet regulatory functions and related physiological and pathological processes, aiming to offer foundational insights for future research into platelet endocytosis.